pengaruh penggunaan kontrasepsi terhadap gangguan menstruasi - zhafira rima wanjaya (Yayasan Pendidikan Medika Indonesia, 2020)
The population growth rate in Indonesia can be controlled through family planning to control fertility. Implementing family planning, of course, uses the contraceptive method. Types of contraception in Indonesia consist of injections, pills, implants, condoms, intra-uterine devices, male operative medical, and female operative media. Where injection is the most popular type of hromonal contraception in developing countries such as Indonesia, amounting to 69.8%. It is known that users of injectable contraceptives, both injection 3 and injection 1 month will experience menstrual disorders. Menstrual disorders that arise in the form of cycle disorders, abnormalities in the amount of blood, the length of bleeding during menstruation, bleeding outside of menstruation, and other disorders that have to do with menstruation. Factors that affect menstruation are hormone factors. Some researchers also said that there was an effect of using hormonal contraceptives such as injection contraception on menstrual disorders.